Spongebob Squarepants. The next 100 episodes Set 2 [videorecording (DVD)] (Paramount Home Entertainment, 2020)
What's funnier than the first 100 episodes of SpongeBob SquarePants? The next 100 (and four) episodes of SpongeBob SquarePants! Grab a hook down to Bikini Bottom to relive all the F.U.N. in this 16-disc collection bubbling with nautical nonsense from the sixth, seventh, eighth and ninth seasons of the hit Nickelodeon series. Viewers will ride a tidal wave of laughter through these fan-favorite legends of the deep.